Intervención optométrica en paciente masculino de 14 años con ambliopía por deprivación. - Contreras Sánchez, Maythe Anais (2024)
The realization of this clinical case focuses on a 14-year-old male patient diagnosed with decreased visual acuity and ocular deviation, a condition in which the patient's vision is affected by a congenital pathology (toxoplasmosis) transmitted by the mother, the diagnosis was not made in time causing amblyopia. The main objective of this work is the optometric intervention to identify the cause of strabic amblyopia due to deprivation and address this problem by improving its visual quality. In this case, optometric examinations are included to identify the symptoms and signs of amblyopia due to deprivation, in which the refractive state, sensory and motor system, the anterior and posterior segment of the cornea and the appendages of the eye where blepharitis was detected in the patient were evaluated, a scar is also visualized by ophthalmoscopy and referred to the specialist who determines by an OCT the congenital pathology of the inactive toxoplasmosis in the patient. Results: Based on these results, a plan of visual therapies and optical treatment is proposed, such as the use of lenses with premiums to improve the alignment of their visual axes. Conclusion: It is intended that, in the optometric intervention, the patient feels the improvement in their vision, reducing the symptoms of amblyopia and improving their visual quality through the indicated treatment.